here is how you go about solving it
first write down the question 3b+4+5b-1
then change arrangement so that it looks like this 3b+5b+4-1
then solve 8b+3
(3b - 4)(3b - 4)
3b -2 =7 b+4
3b+4 = b+12 3b-b = 12-4 2b = 8 b = 4
-7
It is: b+4 when simplified
3b
(3b - 4)(3b - 4)
3b -2 =7 b+4
A plus b 4 can be assumed that mathematically, a = +4.
3b+4 = b+12 3b-b = 12-4 2b = 8 b = 4
-7
It is: b+4 when simplified
4(3b+2)
Think of 2 apples + 3 bananas + 4 apples.What can be added together?6 apples + 3 bananas6a+3b
(3b + 7x)(3b + 7x) or (3b + 7x)2
5 + 10ac + 3b
(a+b)(3b+1)